Global Biodiversity of Aquatic Ammonia-Oxidizing Archaea is Partitioned by Habitat - Biller, Steven J.; Mosier, Annika C.; Wells, George F.; Francis, Christopher A. (Frontiers in Microbiology, 2012)
Archaea play an important role in nitrification and are, thus, inextricably linked to the global carbon and nitrogen cycles. Since the initial discovery of an ammonia monooxygenase α-subunit (amoA) gene associated with an archaeal metagenomic fragment, archaeal amoA sequences have been detected in a wide variety of nitrifying environments. Recent sequencing efforts have revealed extensive diversity of archaeal amoA sequences within different habitats. In this study, we have examined over 8000 amoA sequences from the literature and public databases in an effort to understand the ecological factors influencing the distribution and diversity of ammonia-oxidizing archaea (AOA), with a particular focus on sequences from aquatic habitats. This broad survey provides strong statistical support for the hypothesis that different environments contain distinct clusters of AOA amoA sequences, as surprisingly few sequences are found in more than one habitat type. Within aquatic environments, salinity, depth in the water column, and temperature were significantly correlated with the distribution of sequence types. These findings support the existence of multiple distinct aquatic AOA populations in the environment and suggest some possible selective pressures driving the partitioning of AOA amoA diversity.